Analisis Pengaruh Kebiasaan Berbahasa Daerah dengan Kesalahan Bahasa Indonesia Terhadap Komunikasi Siswa di Sekolah Menengah Pertama - Zalukhu, Cisrad Anda Nita; Lature, Yohanna; Zendrato, Harapan; Maru'ao , Eber Felora; Halawa , Sunida; Harefa, Noveri Amal Jaya (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the influence of habits and the use of regional languages in SMP Negeri 7 Idanogawo. This research is descriptive qualitative research. Data collection techniques in this study, interview and questionnaire techniques. Interviews were conducted with Indonesian language teachers at SMP Negeri 7 Idanogawo and questionnaires were given to 20 students in class VII-A at SMP Negeri 7 Idanogawo. The results of the study show that (1) the acquisition of regional languages by students to other students is more often used than Indonesian in school learning. (2) the impact of regional language learning on students provides positive and negative information. The positive impact of the use of regional languages in learning is that students who study at school use their mother tongue as the language of instruction, tend not to experience difficulties in participating in teaching and learning activities. Meanwhile, the negative impact of using regional languages is: it can make it difficult to use Indonesian in the learning process